Effect of Smoking on Periodontal Health - Visvanathan, Rahul (JCDR Research and Publications (P) Limited, 2014)
Aims and Objectives: The aim of the study was to assess and compare the effect of smoking on mRNA expression of MMP -8 and TIMP-1 in patients with untreated chronic periodontitis and in periodontally healthy subjects and to examine the correlation of MMP-8 and TIMP-1 levels with clinical parameters. Materials and Methods: Out of 60 subjects, 40 were selected subjects for the study, and were divided into Group I (periodontitis subject) and Group II (healthy subjects). Each group was further subdivided into subgroups I-A (chronic periodontitis smokers CPS), and I-B (chronic periodontitis non-smokers CPN), subgroup II-A (healthy smokers HS) and II B (healthy non-smokers HS). Both the groups underwent periodontal examination and clinical parameters were recorded. Tissue samples from both groups were subjected to the isolation of RNA which was then followed by qRT-PCR and the expression of the mRNA levels of MMP-8 and TIMP-1 were analyzed. Results: The mRNA expression of MMP-8 and TIMP-1 was further compared with the periodontal status of all the four groups. The mRNA expression of MMP-8 was compared between the groups and showed that Group I-A (CPS) had higher expression of MMP-8 compared to group I-B (CPN). Group I-B (CPN) vs Group I-A (CPS) showed statistically significant difference in MMP-8/TIMP-1 with higher values for Group I-A (CPS) than Group I-B (CPN). A positive correlation was found between MMP-8 expression and probing depth and clinical attachment level (CAL) among Group I-B (CPN) and Group I-A (CPS) subjects. A significant correlation was also found between MMP-8 and TIMP-1 expression with probing depth and CAL among Group II B(HN) group subjects. TIMP-1 also showed a positive correlation with gingival index (GI) among group II A (HS) subjects. Conclusion: It is concluded that smoking has an impact on the periodontal status and mRNA expression of MMP-8 and TIMP-1 in chronic periodontitis patients. The earlier evaluation of MMP-8 and TIMP-1, can be used as a biomarker in predicting periodontal disease susceptibility.